Digital leadership and green technology for sustainable smart community village transformation: An Islamic economics perspective in Indonesian villages - Gunawan, Ahmad; Kusumah, Dadang Heri; Widiyanti, Widiyanti; Saddaf, Nabila (Universitas Islam Indonesia, 2026)
IntroductionDigital transformation has become a strategic agenda for rural development, particularly in villages that seek to become adaptive, inclusive, and environmentally sustainable Smart Community Villages. However, previous studies have not fully explained how digital leadership drives village transformation through green technology, nor how competence shapes this relationship. In the context of an Islamic economics journal, this issue is also relevant to maslahah, maqasid al-shariah, stewardship, justice, and sustainable welfare.ObjectivesThis study examines the effect of digital leadership on Smart Community Village transformation in Indonesia. It also analyzes the mediating role of green technology and the moderating role of competence in the relationship between digital leadership and sustainable village transformation.MethodThis study used an explanatory quantitative approach with a causal research design. Data were collected through a structured questionnaire from 167 village stakeholders, including village heads, village officials, community leaders, and local changemakers involved in digital transformation and sustainability initiatives. The research model was analyzed using Structural Equation Modeling with Partial Least Squares.ResultsThe results show that digital leadership has a positive and significant effect on Smart Community Village transformation. Green technology also has a significant effect on Smart Community Village transformation and significantly mediates the relationship between digital leadership and village transformation. These findings indicate that digital leadership contributes to sustainable transformation not only directly, but also indirectly through environmentally responsible technological practices. However, competence does not significantly moderate the tested relationships, suggesting that its role may be more complex and context-dependent than a simple interaction effect.ImplicationsThe study implies that village transformation requires leadership capacity, green technology adoption, and systematic competence-building. Policy makers should integrate digital village programs with environmental innovation, digital literacy, inclusive governance, and Islamic economics principles that emphasize public welfare, justice, and ecological stewardship.Originality/NoveltyThis study contributes by integrating digital leadership, green technology, competence, and Smart Community Village transformation into a single empirical model while extending the discussion through an Islamic economics perspective on sustainable rural development.